The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1126/science.2992088
|View full text |Cite
|
Sign up to set email alerts
|

Infection of the Basal Ganglia by a Murine Coronavirus

Abstract: The coronavirus, mouse hepatitis virus strain A59 (MHV-A59), causes mild encephalitis and chronic demyelination. Immunohistochemical techniques showed that MHV-A59-infected C57BL/6 mice contained dense deposits of viral antigen in the subthalamic nucleus and substantia nigra, with fewer signs of infection in other regions of the brain. The animals showed extra- and intracellular vacuolation, neuronal loss, and gliosis in the subthalamic-nigral region. Such localization is unprecedented among known viral enceph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 33 publications
1
48
0
Order By: Relevance
“…These have included a 54-year-old woman who manifested symptoms of parkinsonism while convalescing from meningoencephalitis due to Coxsackie B virus (Walters, 1960) and similar processes have been described following influenza A (Hudson and Rice, 1990), poliovirus (Bojinov 1971) and measles virus (Alves et al, 1992) infections. The possible involvement of virus infection has also been supported by experimental animal models, Fishman et al (1985) reported a selective attack on the substantia nigra and subthalamic nucleus by a strain of mouse hepatitis virus, and more recently similar features have been described in rats infected with influenza virus (Takahashi et al, 1995). In the present study we have demonstrated pathological and to a certain extent clinical features consistent with Parkinson's disease following infection of rats with JEV.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These have included a 54-year-old woman who manifested symptoms of parkinsonism while convalescing from meningoencephalitis due to Coxsackie B virus (Walters, 1960) and similar processes have been described following influenza A (Hudson and Rice, 1990), poliovirus (Bojinov 1971) and measles virus (Alves et al, 1992) infections. The possible involvement of virus infection has also been supported by experimental animal models, Fishman et al (1985) reported a selective attack on the substantia nigra and subthalamic nucleus by a strain of mouse hepatitis virus, and more recently similar features have been described in rats infected with influenza virus (Takahashi et al, 1995). In the present study we have demonstrated pathological and to a certain extent clinical features consistent with Parkinson's disease following infection of rats with JEV.…”
Section: Discussionsupporting
confidence: 68%
“…A second drug associated model of parkinsonism, which involves the stereotactic injection of 6-hydroxydopamine into the substantia nigra, is severely limited by technical difficulties (Kelly et al, 1975). Virusinduced models of Parkinson's disease have been reported following infection with both corona-virus (Fishman et al, 1985) and influenza virus (Takahashi et al, 1995). In this report we describe the development of pathological and certain clinical features consistent with Parkinson's disease following inoculation of Japanese encephalitis virus (JEV).…”
Section: Introductionmentioning
confidence: 98%
“…Only MHVR2 is weakly expressed in the mouse brain (2). This is in contrast to the marked neurotropism of some MHV strains (14,15). Therefore, there may exist other types of MHV receptors in the brain.…”
mentioning
confidence: 43%
“…No bands were detectable in the RNA from the kidney, liver, or intestine (Fig. 6C) (14), whereas some A59 and MHV-3 strains infect restricted areas of the brain (15,30). This finding raises the possibility of the presence of yet another MHV receptor.…”
Section: Methodsmentioning
confidence: 99%
“…Low age at exposure and an inverted V-shaped susceptibility function are supported by epidemiologic observations of childhood age at whooping cough epidemics and PD in Iceland, Creutzfeldt-Jakob disease accidentally transmitted by growthhormone treatment, and dietary exposure to bovine spongiform encephalopathy, as well as age at surgery and risk of sporadic CJD at least 20 years later. The relevance of driver 1 for PD and AD is supported by multiple experimental data relating to: (a) the potential host-tograft induction of AS degeneration from patients diagnosed with PD who received tissue grafts, and disease induction by seeding in the AS and tau mouse models [3,4]; (b) the age-at-exposure-related effect on neurodegeneration induced by neurotropic agents [5,6]; (c) the fact that intracerebral injection of brain extracts containing aggregated AS into young AS-transgenic mice stimulates the formation of AS lesions in the host [7]; and, (d) a similar feature displayed by the male-mouse castration model of PD, which is only efficient when castration is performed on 4-6 week old mice [8]. With regard to this driver, we wonder whether the authors explored a similar experimental approach with younger rats exposed to E. coli curli, with different or clearer results.…”
mentioning
confidence: 99%